2017
DOI: 10.12741/ebrasilis.v10i3.740
|View full text |Cite
|
Sign up to set email alerts
|

Películas de partículas minerais sobre a oviposição da mosca-do-mediterrâneo em laboratório

Abstract: Resumo. Com o intuito de testar a tecnologia de película de partículas minerais com produtos existentes no mercado brasileiro, este trabalho avaliou a ação de caulim e calcário líquido na oviposição de Ceratitis capitata (Wiedemann) (Diptera: Tephritidae). Foram realizados ensaios de laboratório com maçãs e mangas, onde os frutos foram submetidos a pulverizações com caulim e calcário líquido (20% produto + água + espalhante adesivo Break Thru ® ) e controles (água e água + o espalhante adesivo) e expostos, ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…In general, it was verified that the 200 g L −1 suspension inhibited oviposition in choice and non-choice tests. Inhibition of oviposition of C. capitata was also obtained with the use of kaolin (Inducal ® ) and calcareous liquid, applied at the same concentration, in apple and mango fruits [ 71 ]. However, it was observed that 50% of the particle film-based biomaterials in the choice and non-choice tests did not protect the fruits from oviposition by A. obliqua .…”
Section: Discussionmentioning
confidence: 99%
“…In general, it was verified that the 200 g L −1 suspension inhibited oviposition in choice and non-choice tests. Inhibition of oviposition of C. capitata was also obtained with the use of kaolin (Inducal ® ) and calcareous liquid, applied at the same concentration, in apple and mango fruits [ 71 ]. However, it was observed that 50% of the particle film-based biomaterials in the choice and non-choice tests did not protect the fruits from oviposition by A. obliqua .…”
Section: Discussionmentioning
confidence: 99%
“…In this case, the greatest inhibition was achieved with Surround ® , ~19 and 9 times the number of punctures with eggs and number of eggs, respectively. In a suspension at 200 g L −1 , kaolin and liquid limestone applied to apple and mango fruits resulted in an inhibition of C. capitata oviposition (Ourique et al ., 2017). The average number of punctures in apples and mangoes was 7 to 8 times and 3 times lower, respectively, when treated with both products.…”
Section: Discussionmentioning
confidence: 99%